2016
DOI: 10.1098/rspa.2016.0604
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity, passivity and causality in Willis materials

Abstract: Materials that require coupling between the stressstrain and momentum-velocity constitutive relations were first proposed by Willis (Willis 1981 Wave Motion 3, 1-11. (doi:10.1016/0165-2125(81)90008-1)) and are now known as elastic materials of the Willis type, or simply Willis materials. As coupling between these two constitutive equations is a generalization of standard elastodynamic theory, restrictions on the physically admissible material properties for Willis materials should be similarly generalized. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 33 publications
4
59
0
Order By: Relevance
“…Willis coupling is a term in the acoustic and elastic constitutive relations that couples potential and kinetic energy [11][12][13], analogous to the bianisotropy parameter in electromagnetism [14,15]. The Willis coupling and bianisotropy parameters can only be non-zero in structures which lack mirror symmetry about one of their major axes, and their inclusion into the constitutive relations has been shown to resolve violations of causality and passivity in metamaterial homogenization [16,17]. Recent work has demonstrated that the incorporation of Willis coupling or bianisotropy into metamaterial structures of sub-wavelength thickness, known as metasurfaces, can improve their efficiency when refracting at large angles [18][19][20].…”
mentioning
confidence: 99%
“…Willis coupling is a term in the acoustic and elastic constitutive relations that couples potential and kinetic energy [11][12][13], analogous to the bianisotropy parameter in electromagnetism [14,15]. The Willis coupling and bianisotropy parameters can only be non-zero in structures which lack mirror symmetry about one of their major axes, and their inclusion into the constitutive relations has been shown to resolve violations of causality and passivity in metamaterial homogenization [16,17]. Recent work has demonstrated that the incorporation of Willis coupling or bianisotropy into metamaterial structures of sub-wavelength thickness, known as metasurfaces, can improve their efficiency when refracting at large angles [18][19][20].…”
mentioning
confidence: 99%
“…By proper design of the inclusions one can achieve a variety of exotic effective material properties such as negative bulk modulus and density, 1-3 zero index, 4,5 anisotropic and pentamode properties. [6][7][8] Numerous applications have been demonstrated, e.g. acoustic cloaking, 9,10 negative refraction, 11,12 and nonreciprocal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The medium of particular interest in this paper is known as a Willis material, which requires strain-velocity cross-coupling in elasticity or pressure-velocity coupling in acoustics. [15][16][17][18][19] It is well-known that monopole and dipole moments are dominant sources of the scattered field for subwavelength scatterers. For Willis type acoustic scatterers, the scattering requires cross-coupling between pressure and velocity fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another attempt is the proposal to realize Willis media 28 . These media introduce new constitutive terms not only in Hooke's law but also in Newton's second law [29][30][31][32][33] . These terms, which introduce coupling between stress and velocity and between momentum and strain, are typically small perturbations and difficult to realize.…”
mentioning
confidence: 99%